Implementasi Sistem Pembagian Tugas pada Satuan Pendidikan - Makmur Syukri; Facruddin Facruddin; Sonia Purba Tambak; Khairani Khairani; Ahmad Paruqi Hasiholan (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The implementation of tasks in the education unit is considered very important in order to achieve the specified targets. The implementation of tasks is given to systems that are considered capable of carrying them out. The purpose of this study is to analyze the system of task distribution in educational units in islamic boarding schools. This research uses a qualitative approach with a descriptive method. Data collection techniques include interviews with key informants, observations, reference tracing and documentation. Data analysis in this study using data reduction, data presentation (data display), and conclusion drawing by taking into account data validity standards. The results of this research show that the division of tasks in the education unit must be in accordance with professional individuals with the meaning in accordance with their respective expertise / fields. This aims to avoid neglecting the tasks carried out because they cannot be done optimally. Keywords: Education; Boarding; System; Assignment